Dialektika Islam dan Budaya Lokal dalam Tradisi Batamat al-Qur’an Urang Banjar - Saputra, Riza (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
Batamat al-Qur'an is one of several important rituals in the life of Urang Banjar. The Banjarese people commonly perceive Batamat al-Qur'an as a meaningful celebration for their generation, it shows a successful aspect of mastering the holy book al-Qur'an. However, some of the previous local values or pre-Islamic traditions still colorize the process of Batamat al-Qur'an. The previous local value is considered to have positive impacts in Batamat al-Qur’an tradition. The findings of this study, which used a qualitative-descriptive approach, show that the dialectic between the Islamic religion and local culture raises a new meaning and a new contribution form in the life of the Banjarese people. Although Batamat al-Qur'an is a ritual that emphasizes the personal responsibility of Muslims to their God, this tradition has become a ritual that concerns with social aspect wherein the community, residents, and families involve together in Batamat al-Qur'an process.